Assessing the Impact of COVID-19 on Destination Marketing and Image of South Africa - CHUCHU, Tinashe (Journal of Environmental Management and Tourism; Vol 12 No 6 (2021): JEMT Volume XII Issue 6(54) Fall 2021DO - 10.14505//jemt.v12.6(54).04, 2021)
Destination marketing as a research field is attracting an increased amount of attention. The present research provides a review of the impact of COVID-19 on destination marketing of South Africa. The extent to which the COVID-19 pandemic impacted tourist traffic into the country over a selected period in explored. The research utilised government data sources, academic literature and various industry sources to reach its conclusions. The research focused on the period identified to have been the first recorded year of the COVID-19 pandemic spreading globally. The research attempted to comprehensively determine how the global pandemic impacted South Africa’s inbound tourism. Key insights suggested that traffic into the country reduced by half over the identified period both globally and from within the African continent. Suggestions for further research on the topic are proposed.